2014
DOI: 10.1038/pr.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

α-Fetoprotein assay on dried blood spot for hepatoblastoma screening in children with overgrowth-cancer predisposition syndromes

Abstract: Background: Beckwith-Wiedemann syndrome (BWS) and hemihyperplasia (HH) are overgrowth conditions with predisposition to hepatoblastoma for which early diagnosis patients undergo cancer screening based on determination of the tumor marker α-fetoprotein (αFP). Repeated blood draws are a burden for patients with consequent compliance issues and poor adherence to surveillance protocol. We sought to analyze feasibility and reliability of αFP dosage using an analytical micromethod based on blood dried on filter pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…4 Cost-effectiveness of ultrasound screening is proven; 43 we hypothesize that patients with IC1-GoM may benefit from an intensification of abdominal ultrasound during the first Phenotypes in Beckwith-Wiedemann syndrome A Mussa et al 3 years of life, as most of Wilms' tumors are diagnosed before that age and appears justified by their 25% chance of developing a Wilms' tumor, the well-proven beneficial effect of early diagnosis, and the low invasivity of abdominal ultrasound. 44 Conversely, the dosage of the tumor marker serum alpha-fetoprotein as a screening method for the early diagnosis of hepatoblastoma is debated, given the complexity of its interpretation in childhood, 45,46 the low incidence of hepatoblastoma and the invasivity of frequent blood drawns, which is commonly responsible for the lack of adherence to screening protocols. 47 We believe that monitoring is worthwhile at least in UPD patients, given their high risk of hepatoblastoma.…”
Section: Phenotypes In Beckwith-wiedemann Syndromementioning
confidence: 99%
“…4 Cost-effectiveness of ultrasound screening is proven; 43 we hypothesize that patients with IC1-GoM may benefit from an intensification of abdominal ultrasound during the first Phenotypes in Beckwith-Wiedemann syndrome A Mussa et al 3 years of life, as most of Wilms' tumors are diagnosed before that age and appears justified by their 25% chance of developing a Wilms' tumor, the well-proven beneficial effect of early diagnosis, and the low invasivity of abdominal ultrasound. 44 Conversely, the dosage of the tumor marker serum alpha-fetoprotein as a screening method for the early diagnosis of hepatoblastoma is debated, given the complexity of its interpretation in childhood, 45,46 the low incidence of hepatoblastoma and the invasivity of frequent blood drawns, which is commonly responsible for the lack of adherence to screening protocols. 47 We believe that monitoring is worthwhile at least in UPD patients, given their high risk of hepatoblastoma.…”
Section: Phenotypes In Beckwith-wiedemann Syndromementioning
confidence: 99%
“…Few data are currently available on fetal and neonatal growth in BWS, being cancer predisposition the main focus of the available clinical reports (12)(13)(14)(15)(16)(17) given the implications for tumor screening (18)(19)(20). The recent understanding of molecular bases of BWS allowed to define specific correlations between (epi)genotype and phenotype (12)(13)(14)(15)(16)21).…”
mentioning
confidence: 99%
“…Repeated blood draws in early infancy may create a burden for patients and their families, representing an indirect cost and factor affecting compliance. However, a recent survey among parents of patients with BWSp found that parents are often comforted by screening and less invasive methods have been proposed, such as αFP measurement on capillary blood …”
Section: Discussionmentioning
confidence: 99%